2023
DOI: 10.1186/s12967-023-04033-6
|View full text |Cite
|
Sign up to set email alerts
|

Constructing a novel mitochondrial-related gene signature for evaluating the tumor immune microenvironment and predicting survival in stomach adenocarcinoma

Abstract: Background The incidence and mortality of gastric cancer ranks fifth and fourth worldwide among all malignancies, respectively. Accumulating evidences have revealed the close relationship between mitochondrial dysfunction and the initiation and progression of stomach cancer. However, rare prognostic models for mitochondrial-related gene risk have been built up in stomach cancer. Methods In current study, the expression and prognostic value of mitoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(11 citation statements)
references
References 66 publications
1
4
0
Order By: Relevance
“…The validation of our risk score as an autonomous prognostic indicator further emphasizes its utility in clinical settings [ 43 ]. This study contributes a novel, highly accurate tool for prognostic assessment, offering the potential to significantly improve patient management in gastric cancer, highlighting the transformative impact of integrating molecular and computational approaches in the fight against this formidable cancer [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…The validation of our risk score as an autonomous prognostic indicator further emphasizes its utility in clinical settings [ 43 ]. This study contributes a novel, highly accurate tool for prognostic assessment, offering the potential to significantly improve patient management in gastric cancer, highlighting the transformative impact of integrating molecular and computational approaches in the fight against this formidable cancer [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Due to the prominent prognostic relevance of ALDH3A2 in genes associated with fatty acid metabolism pathways, it was chosen as the focus of our study. This gene encodes aldehyde dehydrogenase and plays a critical role in maintaining intracellular redox balance, regulating metabolic pathways, and potentially exerting anti-tumor effects [37] , [38] , [39] . In this context, ALDH3A2 has been found to inhibit lipid accumulation in ccRCC.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 2030 mitochondria-related genes were from Chang et al 23 Mitochondrial-related DEGs (MitoDEGs) were identified by intersecting these genes with the aforementioned DEGs, and graphically displayed using a Venn diagram. Then, the "glmnet" package 24 was applied to explore key MitoDEGs using the least absolute shrinkage and selection operator (LASSO) logistic regression model.…”
Section: Identification Of Hub Mitodegsmentioning
confidence: 99%